Haunting Images : A Cultural Account of Selective Reproduction in Vietnam - Gammeltoft, Tine (Book collections on Project MUSE., 2014)
Based on years of careful ethnographic fieldwork in Hanoi, Haunting Images offers a frank and compassionate account of the moral quandaries that accompany innovations in biomedical technology. At the center of the book are case studies of thirty pregnant women whose fetuses were labeled ""abnormal"" after an ultrasound examination. By following these women and their relatives through painful processes of reproductive decision making, Tine M. Gammeltoft offers intimate ethnographic insights into everyday life in contemporary Vietnam and a sophisticated theoretical exploration of how subjectivit.